Factors Affecting Perceived Economic Growth of Khyber Pakhtunkhwa-Pakistan: A Comparative Study of Formal and Informal Users - Muhammad, Imranullah; Umar, Farooq (2019)
This comparative study ﬁ nds the impact of perceived political, cultural, religious and economic factors on the perceived economic growth of Khyber Pakhtunkhwa, in the users of formal and informal ﬁ nancial systems. A questionnaire was sent to 500 respondents selected as sample for the target population. Out of 500, 369 responded to the questionnaire. After scrutiny, 309 were found valid. The outcome of the study suggested a very strong strategic role of formal and informal ﬁ nancial institutions in economic growth of the province . In this study, users of formal system showed a signiﬁ cant impact of perceived political stability, perceived cultural stability , perceived religious stability and perceived economic growth on the economic growth of the province. In informal ﬁ nancial system users, perceived economic stability, perceived political stability and perceived economic growth has signiﬁ cant impact on the economic growth, where perceived religious stability has insigniﬁ cant impact on economic growth. Difference between Perceived economic stability, Perceived political factors, perceived religious factors, and perceived cultural factors also found insigniﬁ cant across the users of formal and informal ﬁ nancial systems. However, the combination of the results were also associated with present political, cultural, religious and economic factors and the assumed results were debated with more implications at KP province